The role of the study director in nonclinical studies : pharmaceuticals, chemicals, medical devices, and pesticides - Brock, William J.; Mounho, Barbara J.; Fu, Lijie, 1953- (Hoboken, New Jersey : John Wiley & Sons, 2014)
A single-source reference with a broad and holistic overview of nonclinical studies, this book offers critical training material and describes regulations of nonclinical testing through guidelines, models, case studies, practical examples, and worldwide perspectives. The book: Provides a complete overview of nonclinical study organization, conduct, and reporting and describes the roles and responsibilities of a Study Director to manage an effective studyCovers regulatory and scientific concepts, including international testing and Good Laboratory Practice (GLP), compliance with guidelines, an.
Includes index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Medical laboratories -- Quality control; Biological laboratories -- Quality control; Health occupations schools; Allied health personnel -- In-service training; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Allied health personnel -- In-service training; Biological laboratories -- Quality control; Health occupations schools; Medical laboratories -- Quality control; Electronic books; Electronic books